Anaphylaxis admissions in pediatric intensive care units: Follow‐up and risk of recurrence. Issue 3 (20th March 2019) - Pouessel, Guillaume; Cerbelle, Valentine; Lejeune, Stephanie; Leteurtre, Stephane; Ramdane, Nassima; Deschildre, Antoine; ,
Abstract: Background: Data about the risk of anaphylaxis recurrence in children are lacking. We assessed anaphylaxis recurrence and medical follow‐up in a cohort of children previously hospitalized in a French pediatric intensive care unit (PICU) for anaphylaxis. Methods: We conducted a telephone survey of 166 children (≤18 years) hospitalized from 2003 to 2013. Results: In all, 106 (64%) completed the survey (boys, 59%; mean age [SD]: 15.3 years [5.5]). The main index triggers were drugs (45%) and foods (37%). The mean duration follow‐up was of 7.7 years (SD: 2.4). Thirty‐eight (36%) children experienced 399 new allergic reactions during a follow‐up period of 282 patient‐years (incidence rate: 1.4/100 patients/y; 95% CI: 0.64‐2.04). Twelve children experienced 19 anaphylaxis reactions including five requiring PICU admission (anaphylaxis recurrence rate: 0.20/100 patients/y; 95% CI non‐calculable). Food was the trigger for 79% of recurrent reactions and drugs for 8%. The food trigger was previously known in 83%, the same as the index trigger in 69%. Overall, 1.5% of the recurrent reactions were treated with adrenaline injection and 8% an emergency hospital admission. Patients with recurrence had more likely a history of food allergy ( P  < 10 −4 ), asthma ( P  < 0.005), atopic dermatitis ( P  < 0.05) than those without. 31% of the 50 children with food allergy did not see an allergist, 23% had no adrenaline auto‐injector, and 26% lacked a school individual healthcare plan. Conclusions: Following a PICU admission for anaphylaxis, recurrence is high in children with food allergy compared with drug allergy. Allergic comorbidities increase the risk. Medical follow‐up has to be improved for these at‐risk children.